1999
DOI: 10.1055/s-2006-960858
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarials fromStephania venosa, Prismatomeris sessiliflora, Diospyros montanaandMurraya siamensis1

Abstract: Materials and Methods S. officinalis oil, the mixture of alpha-and beta-thujone and chlorhexidine were used as received. All other chemical products were of analytical grade or better. Plant material and oil analyses: S. desoleana and S. sclarea plants came from the Decimoputzu experimental station (Sardinia). Samples of these species, identified by Professor A. D. Atzei, are kept in the Herbarium of the Dipartimento di Scienze del Farmaco; SASSA 1090 bis and 1086, respectively. Oil isolation was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…Antibacterial activity has been shown (Adeniyi et al, 1996;Sanogo et al, 1998). Other Diospyros species showed mainly antimalarial (Likhitwatayawuid et al, 1999), antiinflammatory (Recio et al, 1995), hypotensive (Funayama and Hikino, 1979) and oral antimicrobial (Cai et al, 2000) activities.…”
Section: Discussionmentioning
confidence: 99%
“…Antibacterial activity has been shown (Adeniyi et al, 1996;Sanogo et al, 1998). Other Diospyros species showed mainly antimalarial (Likhitwatayawuid et al, 1999), antiinflammatory (Recio et al, 1995), hypotensive (Funayama and Hikino, 1979) and oral antimicrobial (Cai et al, 2000) activities.…”
Section: Discussionmentioning
confidence: 99%
“…Resonances in the H-COSY spectrum of 4 revealed the connectivity from HÀC(5') to HÀC (7'), and also showed couplings between MeÀC(2) and HÀC (3), and HÀC (6) and HÀC (7). The HMBCspectrum of isodiospyrol A (4) established the partial structure from C(1) to C(8); demonstrating correlations from MeÀC(2) H-atoms to C(1), C(2), and C(3); HÀC (3) to C(4); HOÀC(4) to C(4), C(4a), and C(3); HÀC (6) to C(4a) and C (8); and HÀC (7) to C(5) and C(8a). The HMBC spectral data also assisted in partial structure assembling from C(1') to C (8'), from which the following correlations were seen; HOÀC(1') to C(1'), C(2'), and C(8'a); MeÀC(3') H-atoms to C(2'), C(3'), and C(4'); HÀC(4') to C(5') and MeÀC(3') C-atom; HÀC(5') to C(4'), C(4'a), and C(8'a); and both HÀC(6') and HÀC (7') to C(8').…”
mentioning
confidence: 99%
“…Accumulating lines of evidence reported that the genus Stephania could be a potential source of biologically active compounds which might be used as lead molecules for development of novel drugs (Charles et al, 1987). Tubers of this plant have been used in Thai traditional medicine for nerve tonic, aphrodisiac (Potduang et al, 2003), appetizer and for treatment of asthma, hyperglycemia (Moongkarndi et al, 2004) and anti-malarial activities (Likhitwitayawuid et al, 1999). In addition, some of the isolated alkaloids were reported to exert acetylcholinesterase inhibitors (Ingkaninan et al, 2006), anti-cancer and anti-oxidative activities (Jongsomboonkusol, 2005;Leewanich et al, 2011).…”
Section: Introductionmentioning
confidence: 99%